Matrimonial property in the American states: choice-of-law and conflict-of-laws issues. Issue 1 (15th December 2018) - Stegman, Michael J
Abstract: The itinerant couple raises significant issues for practitioners engaging in planning or estate administration because the couple's acquisition of property often occurs in jurisdictions with differing matrimonial property regimes. This article will treat the private international law of the States of the United States relating to the governing matrimonial property regime of a married couple. The article will first provide an overview of common matrimonial property regimes in the States and in several foreign jurisdictions. Next, the article addresses the couple's freedom, if any, to elect a matrimonial property regime that will be respected as they move among jurisdictions. Finally, the article will cover the differing principles among jurisdictions regarding conflict of matrimonial property laws.